Analisis Status Gizi Siswa di Sekolah Dasar 31 Pasar Ambacang - Ibnu Andli Marta; Suhdy, Muhammad (Silampari Jurnal Olahraga, 2022)
The problem in this research is that out of 164 students, only 74 (45%) students are focused and enthusiastic during the learning process. The purpose of this study was to determine the nutritional status of students at 31 Elementary School Pasar Ambacang Padang City. This research is descriptive research. The population in this study were all students at 31 Pasar Ambacang Elementary School, Padang City, amounting to 164 people. Sampling using proportional stratified random sampling technique, that is, the number of samples obtained is 50 people. To determine the nutritional status of students using the formula BMI = BW/TB2 and for data analysis techniques, namely descriptive analysis P = f/n x 100%. The results showed that the nutritional status of all students, from the discussion, it can be concluded that the nutritional status of 31 Ambacang Elementary School students in Padang City is in the normal category with a percentage of 56%, lean 36%, and fat 8%.